Health Care Expenditure of Rural Households in Pondicherry, India - Poornima Varadarajan (International Journal of Medical Students, 2013)
Background: Shortcomings in healthcare delivery has led people to spend a substantial proportion of their incomes on medical treatment. World Health Organization (2005) estimates reveal that every year 25 million households are forced into poverty by illness and the struggle to pay for healthcare. Thus we planned to calculate the health care expenditure of rural households and to assess the households incurring catastrophic health expenditure. Methods: A cross-sectional study was conducted in the service area of Sri Manakula Vinayagar Medical College and Hospital from May to August 2011. A total of 100 households from the 4 adjoining villages of our Institute were selected for operational and logistic feasibility. The household’s capacity to pay, out of pocket expenditure and catastrophic health expenditure were calculated. Data collection was done using a pretested questionnaire by the principal investigator and the analysis was done using SPSS (version 16). Results: The average income in the highest income quintile was Rs 51,885 but the quintile ratio was 14.98. The median subsistence expenditure was Rs 4,520. About 18% of households got impoverished paying for health care. About 81% of households were incurring out of pocket expenditure and 66% were facing catastrophic health expenses of 40%. Conclusion: There was very high out of pocket spending and a high prevalence of catastrophic expenditure noted. Providing quality care at affordable cost and appropriate risk pooling mechanism are warranted to protect households from such economic threats.